Cosmic ray positron production by gamma ray interactions on starlight - Mastichiadis, A.; Protheroe, R. J.; Stephens, S. A. (Proceedings of the Astronomical Society of Australia, 1991)
The production of cosmic ray positrons by photon-photon pair production of high-energy gamma-rays on starlight photons is examined. Calculating the production rate as a function of positron energy and distance from the sun resulting from interactions with sunlight is the first step. The results are generalized to production on other types of star. The average production rate per unit volume averaged over the local region of the galaxy is calculated, and the contribution to the observed intensity from this process is estimated.
Keywords: cosmic rays; Electromagnetic Interactions; Energetic Particles; Gamma Ray Astronomy; Gamma Ray Spectra; Pair Production; Photons; Plasma-Particle Interactions; Positrons; Space Radiation; Sunlight